2019
DOI: 10.1101/865345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surfactin production is not essential for pellicle and root-associated biofilm development ofBacillus subtilis

Abstract: 20Secondary metabolites have an important impact on the biocontrol potential of soil-21 derived microbes. In addition, various microbe-produced chemicals have been 22 suggested to impact the development and phenotypic differentiation of bacteria, 23including biofilms. The non-ribosomal synthesized lipopeptide of Bacillus subtilis, 24 surfactin, has been described to impact the plant promoting capacity of the bacterium. 25Here, we investigated the impact of surfactin production on biofilm formation of B. 26 sub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(2 reference statements)
1
9
0
Order By: Relevance
“…Our results are in accordance with recent findings, indicating that surfactin is not generally essential for the formation of pellicle biofilms [ 73 ] with surfactin mutants exhibiting similar shifts in the expression of epsA and tapA operons, as we show here for the QS mutant. However, the results presented here suggest that the main regulatory path of biofilm development may include ComX and only subsequently surfactin.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in accordance with recent findings, indicating that surfactin is not generally essential for the formation of pellicle biofilms [ 73 ] with surfactin mutants exhibiting similar shifts in the expression of epsA and tapA operons, as we show here for the QS mutant. However, the results presented here suggest that the main regulatory path of biofilm development may include ComX and only subsequently surfactin.…”
Section: Discussionsupporting
confidence: 94%
“…This could be of clear ecological benefit for the bacterium since surfactin is known to favor motility of multicellular communities and biofilm formation [ 16,28,29 ]. However, a recent study questioned the real role of surfactin in these key functions, since it production appears as non-essential for pellicle biofilm formation in B. subtilis NCIB 3610, suggesting a strain dependant role [ 30 ]. We previously reported that motility and biofilm formation are boosted upon growth on root exudates [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…These experiments thus support that biofilm formation in vitro as well as on plant roots is influenced by additional factors than just matrix gene expression. For example surfactin production, which is regulated by ComA -a target of several Rap phosphatases -was shown to influence the colony structure of B. subtilis 3610 on MSgg, though this secondary metabolite was not essential for pellicle formation and root colonization (Thérien et al, 2020).…”
Section: Discussionmentioning
confidence: 99%